Caracterización de la madera de 95 especies forestales del sur de Ecuador con base a sus propiedades físicas, organolépticas y anatómicas - Cartuche Peralta, Keyla Mabel (2022)
The southern region of Ecuador is known as an area of high biodiversity, where the high variety of forest species is of economic, ecological and cultural importance for the local people. This region confronts problems of deforestation, which diminishes the existing forested areas. Some of the causes are overexploitation and the lack of information on native forest species with potential use. Knowledge of forest species similar to those of high commercial and ecological value helps to achieve sustainable management in order to reduce the pressure of highly exploited species. Therefore, this research studied the similarity of 95 forest species (broadleaf and coniferous) and 84 variables between physical, organoleptic properties, and anatomical characteristics of the wood of each species. For broadleaf species, an unsupervised evaluation and classification was performed by means of Euclidean distance analysis in dendrograms with the use of the statistical programming environment R. Conifers were classified manually due to their small number of four species. Second, the relationship that basic density has on each of the wood properties and characteristics was evaluated. The woods were categorized by density into light, medium-heavy and heavy. The results of the global classification allowed the identification of four groups of woods. The first group was characterized by Laurels (Morella pubescens; Nectandra laurel) and medium weight; the second group by Guayacanes (Handroanthus chrysanthus, H. billbergii and H. serratifolius) and other heavy woods such as Myrcianthes discolor, Lafoensia acuminata, and Chionanthus pubescens; the third group of light woods characterized by the Balsas (Heliocarpus americanus and Ochroma pyramidale); and the fourth group, and the largest group of porous woods characterized by the Cedars (Cedrela montana and C. odorata), Arabiscos (Jacaranda sparrei, J. copaia and J. mimosifolia) and Guabas (Inga marginata, I. oerstediana and I. densiflora). This study also found that basic density is directly related to wood color, fiber cell wall thickness, presence of solitary vessels, presence of rays of two distinct sizes, and various axial parenchyma patterns (aliform, confluent, marginal and non-lignified) which are key characteristics XXI for the identification of woods by density. In conclusion, this study demonstrated that there is a high variability of wood characteristics among forest species in southern Ecuador, and this classification allowed the identification of little-known species with similar potential use to those that are currently highly exploited. Therefore, it is of great importance to generate more information for a greater number of forest species at the regional and national level. And thus, generate new technical data that favor sustainable forest management for better decision making by the actors in charge of the forestry sector in our country. Keywords: wood density, wood anatomy, physical and organoleptic properties, classification.